Chemical composition, morphology, and distribution of particulate matter produced by road pavement abrasion using different types of aggregates and asphalt binder. Issue 1 (1st January 2021) - Jandacka, Dusan; Kovalova, Dasa; Durcanska, Daniela; Decky, Martin
Abstract: This study provides an assessment of the impact of asphalt mixture composition on the particulate matter (PM) emission from the pavement surface into the atmosphere. Pavement surface abrasion was also analyzed and potential differences among asphalt mixtures were determined by the chemical composition of captured PM. Various types of asphalt mixtures and the influence of their compositions on PM concentrations and chemical composition were studied and compared. The laboratory test setup included 12 different pavement samples. On average, the asphalt mixtures with a combination of melaphyre and dolomite as aggregates exhibited the highest values of PM. Measurements of PM2.5 and PM1 in the wheel tracking machine were used to study the impact of asphalt mixture properties on pavement surface abrasion. The dependence between the aggregate used in the tested mixtures and the abraded particulates has been confirmed. The Ca content in aggregates was strongly correlated with the abraded particulates, which was not observed for the Si content. The multidimensional statistical methods used showed the division of markers of the asphalt mixture materials into various factors (sources). The morphology of the solids was examined by electron microscopy with X-ray analysis, indicating the origin of the particles (aggregate, asphalt binder).